Thermostable DNA ligases from hyperthermophiles in biotechnology - Shi, Jingru; Oger, Philippe M.; Cao, Peng; Zhang, Likui (Frontiers in Microbiology, 2023)
DNA ligase is an important enzyme ubiquitous in all three kingdoms of life that can ligate DNA strands, thus playing essential roles in DNA replication, repair and recombination in vivo. In vitro, DNA ligase is also used for biotechnology involved in DNA manipulation, including molecular cloning, mutation detection, DNA assembly, DNA sequencing, and other aspects. Hyperthermophiles thrive in the high-temperature (above 80oC) environments, possessing thermophilic and thermostable enzymes, thus providing an important pool of useful enzymes as biotechnological reagents. Similar to other organisms, each hyperthermophile harbors at least one DNA ligase. In this review, we summarize recent progress on structural and biochemical properties of thermostable DNA ligases from hyperthermophiles, focusing on similarities and differences between DNA ligases from hyperthermophilic bacteria and archaea, and between these thermostable DNA ligases and non-thermostable homologues. Additionally, altered thermostable DNA ligases have been discussed, possessing improved properties compared to the wild-type enzymes, which could be potential DNA ligases for biotechnology in the future. Importantly, we also describe current application of thermostable DNA ligases from hyperthermopiles in biotechnology.